Inventarisasi Plasma Nutfah Serealia Lahan Kering Di Sekitar Kawasan Taman Nasional Kelimutu - Sri Wahyuni; Murdaningsih Murdaningsih (AGRICA, 2011)
The goal of this research was to identify the dryland cereal crop seed plasma types growing around Kelimutu National Park, located in Ende district on the island of Flores in Indonesia, by observing crop morphology and cultivation techniques. Cereal crops represent the largest source of carbohydrates in the regional diet in comparison to other food groups in this area where dry land makes up 80% of the total available land. It is estimated that the Ende district of Flores has adequate potential to produce dryland cereal as a staple food crop. Previous studies have shown that farmer preference is shifting towards the cultivation of crops with a higher economic value which threatens the existence of some cereal crops. Concurrently, shifts in eating habits have made rice a staple food in this region, leading to increased consumption and threatening the existence of other cereal crops. Furthermore, outsiders tend to think of areas like Flores as being impoverished, with frequent problems with food security. Currently, there is a lack of knowledge within the youth population about the types of foods, especially cereals, which are rich in nutrients and their use in rituals. This research aims to address this gap by collecting information on cereal crops in and around Kelimutu National Park for dissemination through educational and cultural tours. This study was conducted in the eastern subdistrict of Ndona, Flores and Wolojita Detusoko between June and December 2011. Study findings identified 5 main cereal crops: paddy fields (consisting of: Are Rumba, Are Sela, Are Obo, Are Laka, Amera, Eko Ndale, Kea Ria, Are Mera, Are Kea Mboa, Eko Ena), corn (consisting of Java Roga, Nggela Java, Java, Keo Ri’a), sorghum (consisting of mera Lolo, Lolo Mite and Lolo Telo Leko), barley (consisting of Mera and Wete Wete Bara) and millet (consisting of Ke’o Mite and Ke’o). Of the five types of cereal crops identified, one type (Pega, a subspecies of barley with a sorghum-like panicle) is not found in four of the districts. It was found that corn, classified as a native plant, is strengthened through cultivation by re-seeding. Study results illustrated that corn in this area is of reduced genetic quality, as illustrated by the fact that 3-4 cobs did not develop. Alternatively, the Ke’o Bara strain of barley has a morphology and panicle strand number (270-300) that suggest that this species is typical of this region.